Evaluation of Building Safety System Aspect Based on Risk (Case Study Building Heritage in Jakarta) - Suwandari, Yunita Dian; Amin, Mawardi; Primatama, Muhammad Agus (AIBPM Publisher, 2021)
Modern and cultural heritage buildings’ safety is mandatory. The damage they suffered, especially the heritage buildings, requires the owners and managers to further improve the supervision of the safety aspects. This study aims to identify, assess, and respond to the safety risk of the heritage buildings. This research was conducted in Jakarta utilizing interviews and questionnaires to identify the risks. Experts and other respondents were deliberately chosen were chosen according to their experience. The risks were analyzed by the probability and weight matrices. This study reveals three high risks and provides the solution to reduce the risk. In addition to academic benefits, the findings are beneficial for the owners and suggest the government carry out risk management.